Attention Disorders Between Impairment and Ferality: Towards a Political Aesth-Ethics of Dismantlement - Citton, Yves (The Nordic Journal of Aesthetics, 2023)
Attention in the 21st century is commonly perceived as being in insufficient supply. Increasing numbers of children and adults are diagnosed with ADHD (Attention Deficit and Hyperactivity Disorder) worldwide. This article suggests that our understanding of attentional deficits could gain from a double reframing. First, the notion of “impairment” (as recently discussed by Jonathan Sterne) seems more appropriate than the category of “disorder” to unfold the stakes of attentional problems. Second, approaching attentional issues as collective and organizational questions seems more empowering than as individual shortcomings—and the notion of “ferality” (as developed by Anna Tsing and the contributors to the Feral Atlas) provides an enlightening tool to account for the role played by infrastructures in the production of attentional deficits. As a result, the article sketches two compasses designed to help us develop a “collapsonaut attention” more in tune with the challenges of the Anthropocene.